The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1159/000497296
|View full text |Cite
|
Sign up to set email alerts
|

Current Advancements in the Development and Characterization of Full-Thickness Adult Neuroretina Organotypic Culture Systems

Abstract: Retinal degenerative diseases such as macular degeneration, glaucoma, and diabetic retinopathy constitute the leading cause of blindness in the industrialized world. There is a continuous demand in investigative ophthalmic research for the development of new treatment modalities for retinal therapy. Unfortunately, efforts to identify novel neuroprotective and neuroregenerative agents have often been hindered by an experimental model gap that exists between high-throughput methods via dissociated cells and prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…In most previous studies, culture periods of 7 to 14 days were used. 22,23 After a comparison of different media on day 12 in culture, the most promising one was identified and longer culture periods were tested. We used a selfdeveloped tissue quality score after immunohistochemistry to receive quantifiable data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most previous studies, culture periods of 7 to 14 days were used. 22,23 After a comparison of different media on day 12 in culture, the most promising one was identified and longer culture periods were tested. We used a selfdeveloped tissue quality score after immunohistochemistry to receive quantifiable data.…”
Section: Discussionmentioning
confidence: 99%
“…4,[12][13][14][15][16][17][18][19][20][21] In most of these studies, organotypic explant cultures have been kept for 7 to 14 days in culture, because the morphological structures at later time points start to deteriorate massively. 22,23 Usually obtained from a butcher or slaughter, the eyeballs are dissected immediately and the retina taken into a culture dish using membrane-based culturing systems. Differences between studies include the orientation of the retina on the membrane 24,25 and several co-culturing options, for example, with the retinal pigment epithelium (RPE).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we showed that our ex vivo axotomy model results in rapid RGC degeneration and gliosis caused by optic nerve transection and disruption of axonal transport, enabling investigation of neuroprotective or anti-inflammatory therapeutic compounds or stem cell transplantation therapies in human or rodent tissues [ 42 , 43 ]. This retinal explant model has the advantage of maintaining an in vivo type architecture with all the neuroretina layers retaining intercellular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate any possible extended time-dependent effects in vitro, we examined retinas harvested 90 or 240 min after enucleation with subsequent culturing for 48 h. The in vitro retinal explant setup is increasingly used for a wide array of research activities, including disease mechanism exploration, pharmacological intervention as well as transplantation [Engelsberg and Ghosh, 2007;Rettinger and Wang, 2018]. Immature retinal porcine tissue can be cultured for extended time periods and even show much of the normal development, however, the adult retina degenerates rapidly within the in vitro environment, which has been attributed to axotomy and the loss of retinal pigment epithelium-photoreceptor contact [Winkler et al, 2002;Engelsberg et al, 2005].…”
Section: Time After Enucleation Has a Significant Impact On Retinal Tissue Damage In Vitromentioning
confidence: 99%
“…The isolated adult retina is extensively used in contemporary research for explorations of pathological disease mechanisms and tissue engineering, as well as in treatment paradigms ranging from pharmacological intervention to experimental retinal transplantation [for a review, see Rettinger and Wang, 2018]. Most experiments have explored retinal tissue from small animals, but research involving large animal models, including porcine and bovine eyes, has gained interest in recent years due to an enhanced similarity to the human retina.…”
Section: Introductionmentioning
confidence: 99%